Flexible high-voltage cable for wind power generation and preparation method thereof
A graphene-based self-healing coating with microcapsules addresses corrosion and flame resistance in marine wind power cables, enhancing durability and mechanical properties.
Patent Information
- Application Number
- CN202510571511.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-07-15
AI Technical Summary
Cables for wind power generation are prone to corrosion in high salt spray environments at sea. The existing technology is difficult to effectively prevent the infiltration of salt spray and lead to electrochemical reactions, which affects the service life.
Chemically grafting flame retardant and styrene triazole on the surface of graphene oxide isoporone diisocyanate to form a microcapsule self-healing agent, and melt blended with crosslinked polyethylene blend to prepare salt spray-resistant sheath material to enhance flexibility and flame retardancy.
Improve the corrosion resistance and flame retardancy of cables in high salt spray environments, enhance flexibility, and repair damaged areas through microcapsule self-healing agents to extend cable life.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-voltage cables, and particularly relates to a flexible high-voltage cable for wind power generation and a preparation method thereof. Background Art
[0002] With the rapid development of global renewable energy technologies, wind power generation has become an important part of the clean energy field. In a wind power generation system, as a key carrier for power transmission, the cable needs to meet the requirements of long-term stable operation in complex environments. The design of cables for wind power generation mostly follows the structure of high-voltage cables in fixed laying scenarios. Their conductors are made of high-purity copper or aluminum stranded wires, the insulating layer is mainly cross-linked polyethylene (XLPE) or ethylene propylene rubber (EPR), and the outer sheath is mostly polyvinyl chloride (PVC) or thermoplastic polyurethane (TPU).
[0003] The Chinese invention patent with the publication number CN117467210B discloses a wind power generation cable with high wear resistance, which includes a cable core wire and a sheath layer arranged in sequence from the inside to the outside. The material of the sheath layer includes polyethylene, ethylene-vinyl acetate copolymer, styrene-butadiene rubber, filling flame retardant, accelerator, heat stabilizer, light stabilizer and lubricant. Compared with the polyethylene cable sheath on the market, this cable sheath layer has higher strength, good heat resistance and excellent electrical insulation, is not prone to cracking, and can ensure the safety of the cable.
[0004] However, in the application of offshore wind power generation, seawater contains high concentrations of chlorides, sulfates, magnesium salts, etc. The breaking of sea waves, evaporation of seawater and strong wind action will bring seawater droplets into the atmosphere, forming a chloride-containing salt mist. When the offshore wind power cable is in this environment for a long time, the salt mist is easy to penetrate into the cross-linked polyethylene protective sleeve and undergo an electrochemical reaction with the metal conductor inside the cable, affecting the service life of the cable. Summary of the Invention
[0005] The purpose of the present invention is to provide a flexible high-voltage cable for wind power generation and a preparation method thereof. By using a chemical grafting method to load a flame retardant and benzotriazole on the surface of graphene oxide, and coating isophorone diisocyanate inside, and then melt-blending with a cross-linked polyethylene blend to obtain a salt mist-resistant sheath material, the problem that the flexible high-voltage cable is easily corroded in a high-salt mist environment is solved, and the effects of enhancing the flexibility, corrosion resistance and flame retardancy of the high-voltage salt mist-resistant sheath material are achieved.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A preparation method of a flexible high-voltage cable for wind power generation, in which an insulating layer, an aluminum foil layer, a shielding layer, and a salt spray-resistant sheath material are sequentially coated outside the inner conductor core to obtain a flexible high-voltage cable for wind power generation. The salt spray-resistant sheath material is prepared by the following steps: Step 1: Generate a hydroxy methoxy cobalt nickel compound on the surface of graphene oxide to obtain a supported flame-retardant graphene oxide powder. Then, react the supported flame-retardant graphene oxide powder with benzotriazole to form a shell, and at the same time, encapsulate isophorone diisocyanate with self-healing function in the shell to obtain a microcapsule self-healing agent.
[0007] Step 2: Modify the microcapsule self-healing agent with a silane coupling agent, and then reduce it with hydrazine hydrate to obtain a modified microcapsule self-healing agent.
[0008] Step 3: Mix the modified microcapsule self-healing agent, crosslinked polyethylene blend, ethylene-vinyl acetate copolymer, ethylene propylene diene monomer, POE grafted maleic anhydride, antioxidant TH-412S, silicone powder, aluminum hydroxide, and light stabilizer evenly, and use a twin-screw extruder to prepare a salt spray-resistant sheath material by melt blending.
[0009] Further, the specific preparation process of the supported flame-retardant graphene oxide powder in Step 1 is as follows: Add cobalt acetate tetrahydrate, nickel acetate tetrahydrate, graphene oxide with a particle size of 100 - 500 nm, and methanol into a reaction kettle, stir at 20 - 25 °C and 500 - 800 r / min for 12 - 14 h, then react at 180 - 190 °C for 48 - 50 h, cool to room temperature, filter, wash, and dry to obtain the supported flame-retardant graphene oxide powder.
[0010] Further, the dosage ratio of cobalt acetate tetrahydrate, nickel acetate tetrahydrate, graphene oxide, and methanol is 10 - 15 g: 1 - 2 g: 20 - 30 g: 300 - 400 mL.
[0011] Further, the specific preparation process of the microcapsule self-healing agent in Step 1 is as follows: Add the supported flame-retardant graphene oxide powder and deionized water into a reaction kettle, ultrasonically disperse, then adjust the pH value to 5 with a 0.1 mol / L ethylenediamine aqueous solution, add a 1 g / L polyvinyl alcohol solution, ultrasonically disperse, mix benzotriazole and isophorone diisocyanate evenly at 50 - 60 °C and add them into the reaction kettle, shear emulsify for 5 - 10 min, stir and react at 40 - 50 °C and 700 r / min for 24 - 26 h, filter, wash, and dry to obtain the microcapsule self-healing agent.
[0012] Furthermore, the dosage ratio of the supported flame-retardant graphene oxide powder, deionized water, polyvinyl alcohol solution, benzotriazole, and isophorone diisocyanate is 8 - 10 g : 4 - 5 L : 1 - 1.2 L : 4 - 5 g : 200 - 230 g.
[0013] Furthermore, the specific preparation process of the modified microcapsule self-healing agent in step two is as follows: Add the microcapsule self-healing agent and absolute ethanol into the reaction kettle, disperse them by ultrasonic wave, adjust the pH value to 3 with 10 wt% ammonia water, then add the silane coupling agent, 95 vol% ethanol solution, and hydrazine hydrate into the reaction kettle, stir at 60 - 70 °C and 300 - 500 r / min for 12 - 14 h, filter, wash, and dry to obtain the modified microcapsule self-healing agent.
[0014] Furthermore, the dosage ratio of the microcapsule self-healing agent, absolute ethanol, silane coupling agent, 95 vol% ethanol solution, and hydrazine hydrate is 4 - 5 g : 500 - 600 mL : 12 - 15 g : 500 - 600 mL : 40 - 42 g.
[0015] Furthermore, the mass ratio of the modified microcapsule self-healing agent, crosslinked polyethylene blend, ethylene-vinyl acetate copolymer, ethylene propylene diene monomer rubber, POE grafted maleic anhydride, antioxidant TH-412S, silicone powder, aluminum hydroxide, and light stabilizer is 1 - 2 : 40 - 50 : 30 - 40 : 10 - 15 : 3 - 5 : 0.3 - 0.8 : 0.8 - 1.2 : 10 - 15 : 0.1 - 0.5. Furthermore, the preparation process of the crosslinked polyethylene blend in step three is as follows: Mix low-density polyethylene, antioxidant 1010, and crosslinkable monomer using a torque rheometer to obtain a blend, add the blend and dicumyl peroxide into the torque rheometer, and mix for 2 - 5 min to obtain the crosslinked polyethylene blend.
[0016] Furthermore, the mass ratio of low-density polyethylene, antioxidant 1010, crosslinkable monomer, and dicumyl peroxide is 40 - 50 : 0.3 - 0.5 : 0.3 - 0.6 : 1 - 2.
[0017] Furthermore, the preparation process of the crosslinkable monomer is as follows: Add CuI, N,N-dimethylethylenediamine, and dimethylformamide into the reaction kettle, stir and react at 20 - 25 °C and 500 - 700 r / min for 20 - 30 min, then add 4,4'-dichlorobenzoyl and maleimide, stir and react at 100 - 110 °C under nitrogen protection for 8 - 9 h, cool to room temperature, filter to remove the precipitate, extract the filtrate, dry, and rotary evaporate to obtain the crosslinkable monomer.
[0018] Further, the dosage ratio of CuI, N,N-dimethylethylenediamine, dimethylformamide, 4,4'-dichlorobenzil and maleimide is 0.3 - 0.5 g : 0.6 - 0.8 g : 180 - 200 mL : 10 - 12 g : 12 - 15 g.
[0019] Beneficial effects of the present invention: In the flexible high-voltage cable for wind power generation of the present invention, the salt spray resistant sheath material is prepared by grafting benzotriazole onto graphene oxide through chemical grafting to form a shell, and simultaneously coating isophorone diisocyanate inside to form a microcapsule self-healing agent. After modification to introduce active groups, it is blended with substances such as cross-linked polyethylene blend through melt blending to obtain the salt spray resistant sheath material. It can play a good corrosion resistance role in the high salt spray and high humidity environment at sea, and has excellent flame retardant effect. At the same time, the modified microcapsule self-healing agent and the cross-linked polyethylene blend will increase the interfacial bonding through hydrogen bonding or chemical cross-linking, and produce a synergistic effect with the cross-linked network structure of the cross-linked polyethylene blend, further improving the flexibility of the cable sheath.
[0020] The microcapsule self-healing agent in the present invention first in-situ grows hydroxy methoxy cobalt nickel compound on the surface of graphene oxide through hydrothermal reaction. During the combustion process, it can catalyze the carbonization of the polymer, generating a denser char residue to wrap on the surface of the polymer, effectively blocking the flame and playing a good flame retardant effect. Then, benzotriazole is connected to graphene oxide through chemical grafting. The -NH group on benzotriazole reacts with the carboxyl group on graphene oxide to form an amide bond, further stabilizing the structure of the microcapsule self-healing agent. At the same time, isophorone diisocyanate is coated inside the microcapsule. When the microcapsule breaks, the isocyanate group in isophorone diisocyanate can react with water in the air to generate amines, and then the amines react with the unreacted isophorone diisocyanate to form polyurea, which can repair the damaged area and restore the barrier performance of the cable, and play a synergistic corrosion resistance role with benzotriazole, improving the corrosion resistance effect of the cable in a high humidity environment.
[0021] 3. The cross-linked polyethylene blend in the present invention first generates cross-linkable monomers through the Goldberg coupling reaction, which has both a carbonyl group capable of introducing deep trap states and an aromatic ketone structure capable of dissipating the energy of high-energy electrons. And under the action of the free radical initiator dicumyl peroxide, a cross-linked structure is generated with low-density ethylene, which can further increase the insulation performance of the salt spray resistant sheath material and form a chemical cross-link with the modified microcapsule self-healing agent, increasing the binding force between the two. Detailed implementation manners
[0022] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0023] Embodiment 1: This embodiment provides a flexible high-voltage cable for wind power generation, which is prepared through the following steps: S1: Add 12.5 g of cobalt acetate tetrahydrate, 1.5 g of nickel acetate tetrahydrate, 25 g of graphene oxide with a particle size of 100 - 500 nm, and 350 mL of methanol into a reaction kettle, stir at 22 °C and 600 r / min for 13 h, then react at 185 °C for 49 h. Hydroxy methoxy cobalt nickel compounds are in-situ grown on the surface of graphene oxide through hydrothermal reaction. Cool to room temperature, centrifuge and filter. Wash the filter cake with methanol 4 times, and vacuum dry at 70 °C for 13 h to obtain supported flame-retardant graphene oxide powder.
[0024] S2: Add 9 g of supported flame-retardant graphene oxide powder and 4.5 L of deionized water into a reaction kettle, ultrasonically disperse for 3.5 h to obtain a dispersion. Then add an aqueous solution of ethylenediamine with a concentration of 0.1 mol / L into the reaction kettle, adjust the pH value to 5. Then add 1.1 L of a polyvinyl alcohol solution with a concentration of 1 g / L into the reaction kettle, ultrasonically disperse for 1.5 h. Mix 4.5 g of benzotriazole and 215 g of isophorone diisocyanate evenly at 55 °C and add them into the reaction kettle, disperse with a high-speed shear machine for 7 min, and react at 45 °C and 600 r / min for 25 h. The -NH group on benzotriazole reacts with the carboxyl group on graphene oxide to form an amide bond, and at the same time, isophorone diisocyanate is coated inside the graphene. Filter, wash the filter cake with acetone 6 times, and dry to constant weight at 45 °C to obtain a microcapsule self-healing agent.
[0025] S3: Add 4.5 g of microcapsule self-healing agent and 550 mL of absolute ethanol into a reaction kettle, ultrasonically disperse for 1.5 h, add ammonia water with a concentration of 10 wt%, adjust the pH value to 3. Then add 13.5 g of silane coupling agent KH-560, 550 mL of ethanol solution with a concentration of 95 vol%, and 41 g of hydrazine hydrate into the reaction kettle, stir at 65 °C and 400 r / min for 13 h to form a Si-O-C bond between the microcapsule self-healing agent and KH-560. Then remove the excess oxygen-containing functional groups on the surface of the microcapsule self-healing agent through a reduction reaction with hydrazine hydrate. Filter, wash the filter cake with absolute ethanol and deionized water 4 times respectively, and dry to constant weight to obtain a modified microcapsule self-healing agent.
[0026] S4: 0.4 g of CuI as a catalyst, 0.7 g of N,N-dimethylethylenediamine and 190 mL of dimethylformamide were added into a reactor, and the reaction was carried out at 22°C and 600 r / min for 25 min. Then, 11 g of 4,4'-dichlorobenzil and 13.5 g of maleimide were added, and the reaction was stirred for 8.5 h at 105°C under nitrogen protection. The mixture was cooled to room temperature, filtered to remove the precipitate, and the filtrate was extracted 4 times with 1 mol / L hydrochloric acid solution, 1 mol / L sodium hydroxide solution and deionized water, respectively. The filtrate was dried over anhydrous magnesium sulfate, and then the filtrate was rotary evaporated to obtain a cross-linkable monomer 1,1'-(oxalylbis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) through a Goldberg coupling reaction.
[0027] S5: The torque rheometer is set to a temperature of 205°C and a speed of 75 r / min, and then 45 g of low-density polyethylene, 0.4 g of antioxidant 1010, and 0.45 g of cross-linkable monomer 1,1'-(oxalylbis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) are mixed using the torque rheometer to obtain a blend. The torque rheometer is then set to a temperature of 205°C and a speed of 75 r / min, and the blend and 1.5 g of diisopropylbenzene peroxide are added to the torque rheometer and mixed for 3 min. The diisopropylbenzene peroxide decomposes to generate alkyl radicals, and the alkyl radicals capture hydrogen atoms from the polymer chain to generate peroxide decomposition products and polymer radicals. Carbon-carbon cross-linking bonds are formed between the polymer radicals to obtain a cross-linked polyethylene blend.
[0028] S6: After uniformly mixing 1.5 parts of modified microcapsule self-healing agent, 45 parts of cross-linked polyethylene blend, 35 parts of ethylene-vinyl acetate copolymer, 12.5 parts of EPDM rubber, 4 parts of POE grafted maleic anhydride, 0.55 parts of antioxidant TH-412S, 1 part of silicone powder, 12.5 parts of aluminum hydroxide, and 0.3 parts of light stabilizer, a salt spray resistant sheath material was prepared by melt blending using a twin-screw extruder granulator, and the modified microcapsule self-healing agent was coated inside the polymer. The die temperature was set to 175°C and the screw speed was set to 175r / min.
[0029] S7: The monofilament conductor is twisted to obtain a conductor core, and the insulating layer (polyethylene), aluminum foil layer, shielding layer (tinned copper braided mesh), and salt spray resistant sheath material are sequentially coated on the outside of the conductor core from the inside to the outside to obtain a flexible high-voltage cable for wind power generation.
[0030] Embodiment 2: This embodiment provides a flexible high-voltage cable for wind power generation, which is prepared by the following steps: S1: Add 10 g of cobalt acetate tetrahydrate, 1 g of nickel acetate tetrahydrate, 20 g of graphene oxide with a particle size of 100 - 500 nm, and 300 mL of methanol into a reaction kettle. Stir at 20 °C and 500 r / min for 12 h, then react at 180 °C for 48 h. In-situ grow hydroxy-methoxy cobalt-nickel compounds on the surface of graphene oxide through hydrothermal reaction. Cool to room temperature, centrifuge and filter. Wash the filter cake with methanol three times and vacuum dry at 60 °C for 12 h to obtain the supported flame-retardant graphene oxide powder.
[0031] S2: Add 8 g of the supported flame-retardant graphene oxide powder and 4 L of deionized water into a reaction kettle. Ultrasonically disperse for 3 h to obtain a dispersion. Then add an aqueous solution of ethylenediamine with a concentration of 0.1 mol / L into the reaction kettle, adjust the pH value to 5. Then add 1 L of a polyvinyl alcohol solution with a concentration of 1 g / L into the reaction kettle and ultrasonically disperse for 1 h. Mix 4 g of benzotriazole and 200 g of isophorone diisocyanate evenly at 50 °C and add them into the reaction kettle. Disperse and process with a high-speed shear machine for 5 min. React at 40 °C and 500 r / min for 24 h. The -NH group on benzotriazole undergoes an amidation reaction with the carboxyl group on graphene oxide to form an amide bond, and at the same time, isophorone diisocyanate is coated inside the graphene. Filter, wash the filter cake with acetone five times, and dry to a constant weight at 40 °C to obtain the microcapsule self-healing agent.
[0032] S3: Add 4 g of the microcapsule self-healing agent and 500 mL of absolute ethanol into a reaction kettle. Ultrasonically disperse for 1 h, add ammonia water with a concentration of 10 wt%, adjust the pH value to 3. Then add 12 g of silane coupling agent KH-560, 500 mL of an ethanol solution with a concentration of 95 vol%, and 40 g of hydrazine hydrate into the reaction kettle. Stir at 60 °C and 300 r / min for 12 h to form Si-O-C bonds between the microcapsule self-healing agent and KH-560, and then remove the excess oxygen-containing functional groups on the surface of the microcapsule self-healing agent through a reduction reaction with hydrazine hydrate. Filter, wash the filter cake with absolute ethanol and deionized water three times respectively, and dry to a constant weight to obtain the modified microcapsule self-healing agent.
[0033] S4: 0.3 g of CuI as a catalyst, 0.6 g of N,N-dimethylethylenediamine and 180 mL of dimethylformamide were added into a reactor, and the reaction was carried out at 20°C and 500 r / min for 20 min. Then, 10 g of 4,4'-dichlorobenzil and 12 g of maleimide were added, and the reaction was stirred for 8 h at 100°C under nitrogen protection. The mixture was cooled to room temperature, filtered to remove the precipitate, and the filtrate was extracted 3 times with 1 mol / L hydrochloric acid solution, 1 mol / L sodium hydroxide solution and deionized water, respectively. The filtrate was dried over anhydrous magnesium sulfate, and then the filtrate was rotary evaporated to obtain a cross-linkable monomer 1,1'-(oxalylbis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) through a Goldberg coupling reaction.
[0034] S5: The torque rheometer is set to a temperature of 200°C and a speed of 50 r / min, and then 40 g of low-density polyethylene, 0.3 g of antioxidant 1010, and 0.3 g of cross-linkable monomer 1,1'-(oxalylbis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) are mixed using the torque rheometer to obtain a blend. The torque rheometer is then set to a temperature of 200°C and a speed of 50 r / min, and the blend and 1 g of diisopropylbenzene peroxide are added to the torque rheometer and mixed for 2 min. The diisopropylbenzene peroxide decomposes to generate alkyl radicals, and the alkyl radicals capture hydrogen atoms from the polymer chain to generate peroxide decomposition products and polymer radicals. Carbon-carbon cross-linking bonds are formed between the polymer radicals to obtain a cross-linked polyethylene blend.
[0035] S6: After uniformly mixing 1 part of modified microcapsule self-healing agent, 40 parts of cross-linked polyethylene blend, 30 parts of ethylene-vinyl acetate copolymer, 10 parts of EPDM rubber, 3 parts of POE grafted maleic anhydride, 0.3 parts of antioxidant TH-412S, 0.8 parts of silicone powder, 10 parts of aluminum hydroxide and 0.1 parts of light stabilizer, a salt spray resistant sheath material was prepared by melt blending using a twin-screw extruder granulator, and the modified microcapsule self-healing agent was coated inside the polymer. The die temperature was set to 170°C and the screw speed was set to 150r / min.
[0036] S7: The monofilament conductor is twisted to obtain a conductor core, and the insulating layer (polyethylene), aluminum foil layer, shielding layer (tinned copper braided mesh), and salt spray resistant sheath material are sequentially coated on the outside of the conductor core from the inside to the outside to obtain a flexible high-voltage cable for wind power generation.
[0037] Embodiment 3: This embodiment provides a flexible high-voltage cable for wind power generation, which is prepared by the following steps: S1: Add 15 g of cobalt acetate tetrahydrate, 2 g of nickel acetate tetrahydrate, 30 g of graphene oxide with a particle size of 100 - 500 nm, and 400 mL of methanol into a reaction kettle. Stir at 25 °C and 800 r / min for 14 h, then react at 190 °C for 50 h. In-situ grow hydroxy-methoxy cobalt nickel compounds on the surface of graphene oxide through hydrothermal reaction. Cool to room temperature, centrifuge and filter. Wash the filter cake with methanol 5 times, and vacuum dry at 80 °C for 14 h to obtain the supported flame-retardant graphene oxide powder.
[0038] S2: Add 10 g of the supported flame-retardant graphene oxide powder and 5 L of deionized water into a reaction kettle, and ultrasonically disperse for 4 h to obtain a dispersion. Then add an aqueous solution of ethylenediamine with a concentration of 0.1 mol / L into the reaction kettle, adjust the pH value to 5. Then add 1.2 L of a polyvinyl alcohol solution with a concentration of 1 g / L into the reaction kettle, and ultrasonically disperse for 2 h. Mix 5 g of benzotriazole and 230 g of isophorone diisocyanate evenly at 60 °C and add them into the reaction kettle, and disperse and process with a high-speed shear machine for 10 min. React at 50 °C and 700 r / min for 26 h. The -NH group on benzotriazole and the carboxyl group on graphene oxide undergo an amidation reaction to form an amide bond, and at the same time, isophorone diisocyanate is coated inside the graphene. Filter, wash the filter cake with acetone 7 times, and dry to constant weight at 50 °C to obtain the microcapsule self-healing agent.
[0039] S3: Add 5 g of the microcapsule self-healing agent and 600 mL of absolute ethanol into a reaction kettle, and ultrasonically disperse for 2 h. Add ammonia water with a concentration of 10 wt%, and adjust the pH value to 3. Then add 15 g of silane coupling agent KH-560, 600 mL of an ethanol solution with a concentration of 95 vol%, and 42 g of hydrazine hydrate into the reaction kettle, and stir at 70 °C and 500 r / min for 14 h to form a Si-O-C bond between the microcapsule self-healing agent and KH-560. Then remove the excess oxygen-containing functional groups on the surface of the microcapsule self-healing agent through a reduction reaction with hydrazine hydrate. Filter, wash the filter cake with absolute ethanol and deionized water 5 times respectively, and dry to constant weight to obtain the modified microcapsule self-healing agent.
[0040] S4: Add 0.5 g of CuI as a catalyst, 0.8 g of N,N-dimethylethylenediamine, and 200 mL of dimethylformamide into a reaction kettle, react for 30 min under the conditions of 25 °C and 700 r / min, then add 12 g of 4,4'-dichlorobenzil and 15 g of maleimide, stir and react for 9 h under nitrogen protection and at 110 °C, cool to room temperature, filter to remove the precipitate, extract the filtrate 5 times with a hydrochloric acid solution with a concentration of 1 mol / L, a sodium hydroxide solution with a concentration of 1 mol / L, and deionized water respectively, dry the filtrate with anhydrous magnesium sulfate, then rotary evaporate the filtrate, and obtain the crosslinkable monomer 1,1'-(oxybis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) through the Goldberg coupling reaction.
[0041] S5: Set the torque rheometer to a temperature of 210 °C and a rotation speed of 100 r / min, then mix 50 g of low-density polyethylene, 0.5 g of antioxidant 1010, and 0.6 g of the crosslinkable monomer 1,1'-(oxybis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) using the torque rheometer to obtain a blend. Then set the torque rheometer to a temperature of 210 °C and a rotation speed of 100 r / min, add the blend and 2 g of dicumyl peroxide into the torque rheometer, and mix for 5 min. Dicumyl peroxide decomposes to generate alkyl radicals, and the alkyl radicals abstract hydrogen atoms from the polymer chain to generate peroxide decomposition products and polymer radicals. Carbon-carbon crosslinking bonds are formed between the polymer radicals to obtain a crosslinked polyethylene blend.
[0042] S6: After uniformly mixing 2 parts of the modified microcapsule self-healing agent, 50 parts of the crosslinked polyethylene blend, 40 parts of ethylene-vinyl acetate copolymer, 15 parts of ethylene propylene diene monomer rubber, 5 parts of POE grafted maleic anhydride, 0.8 part of antioxidant TH-412S, 1.2 parts of silicone powder, 15 parts of aluminum hydroxide, and 0.5 part of light stabilizer, use a twin-screw extruder to prepare a salt spray-resistant sheath material through melt blending. The modified microcapsule self-healing agent is coated inside the polymer, and the die head temperature is set to 180 °C and the screw rotation speed is set to 200 r / min.
[0043] S7: Strand the single-wire conductor to obtain the conductor inner core, and sequentially coat the insulating layer (polyethylene), aluminum foil layer, shielding layer (tinned copper braided mesh), and salt spray-resistant sheath material outside the conductor inner core from the inside to the outside to obtain a flexible high-voltage cable for wind power generation.
[0044] The light stabilizer used in Examples 1-3 of this embodiment is BW-10LD (poly(butanedioic acid (4-hydroxyethyl-2,2,6,6-tetramethyl-1-piperidinoethanol) ester)), and the rest of the raw materials are commercially available products.
[0045] Comparative Example 1: On the basis of Example 1, the modified microcapsule self-healing agent was removed in S6, and the remaining steps remained unchanged, and a flexible high-voltage cable for wind power generation was prepared.
[0046] Comparative Example 2: On the basis of Example 1, graphene oxide powder was used to replace the supported flame-retardant graphene oxide powder in S2, and the remaining steps remained unchanged, and a flexible high-voltage cable for wind power generation was prepared.
[0047] Comparative Example 3: On the basis of Example 1, graphene oxide microcapsules were used to replace the microcapsule self-healing agent in S3, and the remaining steps remained unchanged, and a flexible high-voltage cable for wind power generation was prepared.
[0048] Comparative Example 4: On the basis of Example 1, crosslinked polyethylene was used to replace the crosslinked polyethylene blend in S6, and the remaining steps remained unchanged, and a flexible high-voltage cable for wind power generation was prepared.
[0049] The flexible high-voltage cables for wind power generation in Examples 1 - 3 and Comparative Examples 1 - 4 were subjected to performance tests: Flame retardancy performance: The limiting oxygen index test was carried out using a limiting oxygen index instrument (Nanjing Jiangning Analytical Instrument Factory, JF-3 type). According to GB / T 2406.2-2009, the sample specification was 100mm×6.5mm×3mm, with five samples in each group, and the average value was taken. The LOI represents the limiting oxygen index.
[0050] Salt spray resistance performance: The salt spray test was carried out on the complete flexible high-voltage cable and the scratched flexible high-voltage cable in accordance with the ASTM B117 international standard. The test time was 500h, and the test conditions were as follows: the concentration of sodium chloride solution in the salt spray chamber was 5wt%, the test temperature was 35°C, the pressure in the salt spray chamber was 10psi. Scratches with a length of 2cm and a width of 3μm were made on the surface of the high-voltage cable using a blade. The complete flexible high-voltage cable and the scratched flexible high-voltage cable were respectively immersed in a 5wt% NaCl salt solution.
[0051] Mechanical properties: An electronic universal testing machine: CMT type (MTS Industrial Systems Co., Ltd.) was used. It was carried out according to the GB / T9341-2008 standard. The specimen length was 80mm, the width was 10mm, the thickness was 4mm, the speed was set to 2mm / min, and the deflection was set to 6mm.
[0052] Insulation performance: According to the international standard IEC 60243, a DC breakdown experiment was carried out on the specimen using a DC breakdown system. Cylindrical-plate electrodes were used, and the electrode size was such that the upper electrode diameter was 25mm, the lower electrode diameter was 75mm, and both edges of the two electrodes had 5mm rounded corners. A circular film specimen with a thickness of 50μm and a diameter of 100mm was used.
[0053] Table 1 Performance test result table Project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 LOI (%) 35.5 35.2 35.8 15.5 21.2 21.5 35.4 <![CDATA[Low-frequency impedance value (×10 6 Ω·cm 2 )]]> 4.96 5.04 4.86 2.11 4.83 2.15 4.94 Flexural Strength (MPa) 6.2 6.5 6.0 15.5 6.7 6.8 8.2 DC Characteristic Breakdown Field Strength (kV / mm) 440.6 445.2 442.7 441.9 443.1 442.3 263.5 As can be seen from Table 1, the LOI (limiting oxygen index) in Examples 1 - 3 is higher than that in Comparative Examples 1 - 3. At the same time, the LOI of Comparative Example 1 is higher than that of Comparative Examples 2 and 3. No modified microcapsule self-healing agent was added in Comparative Example 1, and its flame retardant performance is the worst. In Comparative Example 2, graphene oxide powder was used instead of the supported flame-retardant graphene oxide powder, and in Comparative Example 3, graphene oxide microcapsules were used instead of the microcapsule self-healing agent, and their flame retardant effects are second. This shows that graphene oxide and the supported flame-retardant graphene oxide powder have a synergistic effect in improving the flame retardant performance of flexible high-voltage cables for wind power generation.
[0054] The low-frequency impedance values in Examples 1 - 3 and Comparative Example 2 are higher than those in Comparative Examples 1 and 3, indicating that Examples 1 - 3 and Comparative Example 2 have the best corrosion resistance. In Comparative Example 2, graphene oxide powder was used instead of the supported flame-retardant graphene oxide powder, and in Comparative Example 3, graphene oxide microcapsules were used instead of the microcapsule self-healing agent, indicating that the addition of the microcapsule self-healing agent can improve the corrosion resistance of flexible high-voltage cables for wind power generation.
[0055] The flexural strengths of Examples 1 - 3 and Comparative Examples 2 - 3 are all lower than that of Comparative Example 1, and the flexural strength in Comparative Example 4 is at an intermediate value, indicating that Examples 1 - 3 and Comparative Examples 2 - 3 have better flexibility. In Comparative Example 1, the modified microcapsule self-healing agent was removed, and in Comparative Example 4, crosslinked polyethylene was used instead of the crosslinked polyethylene blend, indicating that a chemical bond was formed between the modified microcapsule self-healing agent and the crosslinked polyethylene blend, and the two have a synergistic effect in improving the flexibility of flexible high-voltage cables for wind power generation.
[0056] The DC characteristic breakdown field strengths of Examples 1 - 3 and Comparative Examples 1 - 3 are higher than that of Comparative Example 4, indicating that Examples 1 - 3 and Comparative Examples 1 - 3 have better insulation. In Comparative Example 4, crosslinked polyethylene was used instead of the crosslinked polyethylene blend, indicating that the crosslinked polyethylene blend increases the insulation of the salt spray resistant sheath material.
[0057] It should be noted that in this article, terms such as "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or further includes elements inherent to such process, method, article or device.
[0058] Although the embodiments of the present invention have been shown and described, those of ordinary skill in the art can understand that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention.
Claims
1. A preparation method of a flexible high-voltage cable for wind power generation, the preparation method comprising: An insulating layer, an aluminum foil layer, a shielding layer, and a salt spray-resistant sheath material are sequentially coated outside the inner core of the conductor from the inside to the outside. It is characterized in that the salt spray-resistant sheath material is prepared by the following steps: Step 1: Hydroxy methoxy cobalt nickel compound is generated on the surface of graphene oxide to obtain a supported flame-retardant graphene oxide powder. Then, the supported flame-retardant graphene oxide powder and benzotriazole are reacted to form a shell, and isophorone diisocyanate is wrapped in the shell at the same time to obtain a microcapsule self-healing agent; Step 2: The microcapsule self-healing agent is modified by a silane coupling agent and then reduced by hydrazine hydrate to obtain a modified microcapsule self-healing agent; Step 3: The modified microcapsule self-healing agent, cross-linked polyethylene blend, ethylene-vinyl acetate copolymer, ethylene propylene diene monomer, POE grafted maleic anhydride, antioxidant TH-412S, silicone powder, aluminum hydroxide, and light stabilizer are mixed evenly, and a salt spray-resistant sheath material is prepared by melt blending using a twin-screw extruder granulator.
2. The preparation method of a flexible high-voltage cable for wind power generation according to claim 1, wherein, The specific preparation process of the supported flame-retardant graphene oxide powder in Step 1 is as follows: Cobalt acetate tetrahydrate, nickel acetate tetrahydrate, graphene oxide, and methanol are added to a reaction kettle, stirred at 20-25 °C and 500-800 r / min for 12-14 h, then reacted at 180-190 °C for 48-50 h, cooled to room temperature, filtered, washed, and dried to obtain a supported flame-retardant graphene oxide powder.
3. The preparation method of a flexible high-voltage cable for wind power generation according to claim 2, characterized in that The dosage ratio of cobalt acetate tetrahydrate, nickel acetate tetrahydrate, graphene oxide, and methanol is 10-15 g: 1-2 g: 20-30 g: 300-400 mL.
4. The preparation method of a flexible high-voltage cable for wind power generation according to claim 1, characterized in that, The specific preparation process of the microcapsule self-healing agent in Step 1 is as follows: The supported flame-retardant graphene oxide powder and deionized water are added to a reaction kettle, ultrasonically dispersed, the pH value is adjusted to 5 with an ethylenediamine aqueous solution, a polyvinyl alcohol solution with a concentration of 1 g / L is added, ultrasonically dispersed, benzotriazole and isophorone diisocyanate are mixed evenly at 50-60 °C and then added to the reaction kettle, shear emulsified for 5-10 min, stirred and reacted at 40-50 °C and 700 r / min for 24-26 h, filtered, washed, and dried to obtain a microcapsule self-healing agent; The dosage ratio of the supported flame-retardant graphene oxide powder, deionized water, polyvinyl alcohol solution, benzotriazole, and isophorone diisocyanate is 8-10 g: 4-5 L: 1-1.2 L: 4-5 g: 200-230 g.
5. The preparation method of a flexible high-voltage cable for wind power generation according to claim 1, characterized in that, The preparation process of the modified microcapsule self-healing agent in Step 2 is as follows: The microcapsule self-healing agent and absolute ethanol are added to a reaction kettle, ultrasonically dispersed, the pH value is adjusted to 3 with ammonia water, then the silane coupling agent, ethanol solution with a concentration of 95 vol%, and hydrazine hydrate are added to the reaction kettle, stirred at 60-70 °C and 300-500 r / min for 12-14 h, filtered, washed, and dried to obtain a modified microcapsule self-healing agent.
6. The preparation method of a flexible high-voltage cable for wind power generation according to claim 5, characterized in that, The dosage ratio of the microcapsule self-healing agent, absolute ethanol, silane coupling agent, 95 vol% ethanol solution, and hydrazine hydrate is 4-5 g: 500-600 mL: 12-15 g: 500-600 mL: 40-42 g.
7. The preparation method of a flexible high-voltage cable for wind power generation according to claim 1, characterized in that, The mass ratio of the modified microcapsule self-healing agent, crosslinked polyethylene blend, ethylene-vinyl acetate copolymer, ethylene propylene diene monomer, POE grafted maleic anhydride, antioxidant TH-412S, silicone powder, aluminum hydroxide and light stabilizer described in step three is 1-2:40-50:30-40:10-15:3-5:0.3-0.8:0.8-1.2:10-15:0.1-0.
5.
8. The preparation method of a flexible high-voltage cable for wind power generation according to claim 1, characterized in that, The preparation process of the crosslinked polyethylene blend described in step three is as follows: Mix low-density polyethylene, antioxidant 1010 and crosslinkable monomer using a torque rheometer to obtain a blend. Add the blend and dicumyl peroxide into the torque rheometer and mix for 2-5 min to obtain a crosslinked polyethylene blend; The mass ratio of the low-density polyethylene, antioxidant 1010, crosslinkable monomer and dicumyl peroxide is 40-50:0.3-0.5:0.3-0.6:1-2.
9. The preparation method of a flexible high-voltage cable for wind power generation according to claim 8, characterized in that, The preparation process of the crosslinkable monomer is as follows: Add CuI, N,N-dimethylethylenediamine and dimethylformamide into a reaction kettle, stir and react at 20-25 °C and 500-700 r / min for 20-30 min. Then add 4,4'-dichlorobenzil and maleimide, and stir and react under nitrogen protection at 100-110 °C for 8-9 h. Cool to room temperature, filter to remove the precipitate, extract the filtrate, dry it, and perform rotary evaporation to obtain the crosslinkable monomer; The dosage ratio of CuI, N,N-dimethylethylenediamine, dimethylformamide, 4,4'-dichlorobenzil and maleimide is 0.3-0.5 g:0.6-0.8 g:180-200 mL:10-12 g:12-15 g.
10. A flexible high-voltage cable for wind power generation, characterized in that, It is prepared by the preparation method of a flexible high-voltage cable for wind power generation according to any one of claims 1-9.
Citation Information
Patent Citations
A wind power cable with high wear resistance
CN117467210B
Cited By
Temperature-resistant and wear-resistant three-layer insulated wire and preparation method thereof
CN120674164A